Diseño e implementación de un prototipo de sistema de gestión inalámbrico de atención al cliente. - Reyes Ramírez, Tatiana Carolina (2015)
The present thesis project is focused on the automation of the management system of traditional customer service, based on the construction of a wireless management system prototype which allows the interactive communication, flexible and reliable between the customer and the business manager. The design of the system is destined to be implemented in bars, marketing selection chosen by simple preference. The design is divided in three sections, the first section constitutes the configuration of the wireless network, the second section is the user interface and the third section is the administrator interface. The configured wireless network is a multipoint network constituted by a coordinator unit XBee and two terminal units. The interface of each user is designed with the platform of Arduino equipment made up of a touch screen TFT LCD for the display and selection of the request, a metal sheet Arduino Mega 2560 R3 used for the digital processing of the received signs, and a Shield TFT LCD Mega for the adjustment of the metal sheet Arduino with the touch screen as well as the corresponding the unit XBee for the wireless communication with the administrator. The section of the administrator interface is designed with the software Matlab, through a GUIDE which allows visualizing the data reception in an appropriate way, its implementation belongs to a computer and the coordinator unit XBee for the wireless communication with the user.